Expression of Nectin-4 in chromophobe renal cell carcinoma in a multicenter cohort: early prognostic and therapeutic considerations - Mikuteit, Marie; Zschäbitz, Stefanie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (Oncology, 2024)
Introduction: Nectin-4 is a member of the nectin family and a calcium-independent immunoglobulin-like transmembrane protein that contributes to tumor growth and angiogenesis in malignant tumors. A nectin-4-directed antibody drug conjugate, enfortumab vedotin-ejf, has recently been approved for treatment in urothelial cancer and is currently under investigation in other tumor entities such as breast, lung, and prostate cancer. In non-clear cell renal cell carcinoma (RCC), vascular endothelial growth factor (VEGF)-directed tyrosine kinase inhibitors and checkpoint inhibitors are currently treatments of choice. However, due to the rarity of disease treatment recommendations for chromophobe RCC (chRCC) are limited and new therapeutic agents urgently needed. In this study, we investigated the expression and prognostic impact of nectin-4 in a large cohort of chRCC. Methods: Patients who underwent renal surgery due to chRCC were recruited. Clinical data were retrospectively evaluated. Tumor specimen was analyzed for nectin-4 expression by immunohistochemistry. Results: Eighty-one chRCC patients were eligible for analysis. In 15 (18.5%) samples, tumors were positive for nectin-4. No significant associations were found for nectin-4 expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis disclosed a 5-year overall survival for nectin-4-negative and nectin-4-positive tumors of 91.8% versus 100.0% (p = 0.316, log rank). Conclusions: In chRCC, a small subset of tumors expresses nectin-4 potentially amenable to nectin-4-directed treatment. Expression of nectin-4 is not associated with parameters of aggressiveness or survival. Due to the rare incidence of chRCC, further studies with larger cohorts are warranted.
Online veröffentlicht: 01. Dezember 2023
Gesehen am 29.07.2024